MODUL BELAJAR SCHOOL FROM HOME UNTUK MEMBANTU PEMBELAJARAN DARI RUMAH - Wardana, Aditia Eska; Purwandari, Septiyati (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The aim of this research is to develop teaching materials in the form of school from home learning modules in the hope of providing solutions to solve these problems.The research method used is the Research and Development (RD) which consists of a preliminary study stage, a development stage and an evaluation stage. Research respondents were teachers, students, and parents of students. The model is validated by experts and practitioners with the Delphi technique. The practicality of the model was tested with quantitative descriptive techniques that measure the practicality of using the module and its usefulness by giving questionnaires to respondents to students and parents as product users. The results showed that: (1) The School From Home Module Design is a module made by considering the material, expanding exploration, and using objects at home and the environment as a medium. (2) the validity of the school from home module got a percentage value of 83% in the very good category. (3) the overall practicality trial obtained a percentage of 86% in the very practical category.